Implementation of Development of Narcotics Prisoners at the Binjai Class IIA Penitentiary - Oktri Silfia (LEGAL BRIEF, 2018)
In general, the development of narcotics convicts at the Binjai Class IIA Penitentiary aims to make them fully human as has been the direction of national development. The problem posed is how the implementation of guidance provided by the Class II A Binjai Prison for inmates who commit crimes of narcotics abuse; The research method or type of this research is Normative Empirical which is descriptive analysis, namely describing, describing, analyzing and explaining the analysis of the problems raised. The data needed in this study are primary data whose sources come from sources or respondents, and secondary data from the source. originating from legislation, the work of the general public and various literature that support this research. The results of the study can be concluded that the Implementation of Narcotics Abuse Prisoners at the Binjai Class IIA Penitentiary is a program that combines various methods including medical, social, spiritual and skills aspects, which aim to make narcotics convicts a better person for their family and Public.